Protocol for reconstructing ancestral genomes from present-day samples by applying local ancestry inference - Xiaoxi Zhang; Baonan Wang; Jia Wen; Yang Gao; Yuwen Pan; Shuhua Xu (STAR Protocols)
Summary: The genome of the most recent common ancestor is generally not available but can greatly facilitate the inference of demographic history and the detection of local adaptations. Here, we present a protocol for applying local ancestry inference in present-day samples to reconstruct ancestral genomes. We describe steps for estimating haplotypes, inferring local ancestry, and assembling ancestral haplotypes. This protocol describes the analytic steps of reconstructing ancestral genomes using the example data of the Miao and She target populations.For complete details on the use and execution of this protocol, please refer to Gao et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.